Synthsizer Audio Generator Analysist (Saga) DVOR Maru 220 Menggunakan Arduino Uno - Bagus Harianto, Bambang; Putri Aulia, Gesti; Silk Moonlight, Lady; Faizal Rizali, Dion; Ardi Firmansyah, Rahman (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2025)
This study aims to design and implement a portable device based on the Arduino Uno ATmega328P microcontroller that is able to read and analyze the output signal from the DVOR Maru 220 Modulation Signal Generator (MSG) MODULE. This tool was developed to detect three main types of frequency signals, namely 30 Hz (reference signal), 720 Hz (blending signal), and 1020 Hz (ident signal), which play an important role in DVOR navigation systems. Data acquisition is done via an Arduino analog input and displayed in real-time via a desktop-based PyQt5 interface. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model approach. The test results showed that the SAGA system was able to display frequency data with a fairly good level of accuracy, with the lowest deviation of 0.3973% at the frequency of 720 Hz. This system was considered effective in assisting technicians in the process of diagnosis, maintenance, and calibration of MSG Modules without having to use conventional equipment that was not portable. This innovation provides an efficient and economical solution in supporting DVOR-based navigation device maintenance activities.